Neotropical Meliponini: Paratrigonoides mayri, new genus and species from western Colombia (Hymenoptera, Apidae, Apinae) and phylogeny of related genera - Camargo, João M.f.; Roubik, David W. (Zootaxa, 2005)
Paratrigonoides mayri gen. nov., sp. nov., from the Cauca Valley region of Antioquia, Colombia, is described. It resembles Paratrigona, especially species of the P. lineata group. The new genus is recognized by a combination of bidentate mandibles, the keirotrichiate area of tibia III not depressed on the posterior edge (plesiomorphies), yellow markings flanking the frontal median line and two spots below the lateral ocelli, supraclypeal area partly covering antennal sockets, and by the upper part of the preoccipital ridge lamellate and bordered by a row of robust hairs (autapomorphies). The result of a cladistic analysis suggests Paratrigona +Aparatrigona form the sister-group of Paratrigonoides gen. nov.